Beyond burial: lateral exchange is a significant atmospheric carbon sink in mangrove forests. (31st July 2018) - Maher, Damien T.; Call, Mitchell; Santos, Isaac R.; Sanders, Christian J.
Abstract : The blue carbon paradigm has evolved in recognition of the high carbon storage and sequestration potential of mangrove, saltmarsh and seagrass ecosystems. However, fluxes of the potent greenhouse gases CH4 and N2 O, and lateral export of carbon are often overlooked within the blue carbon framework. Here, we show that the export of dissolved inorganic carbon (DIC) and alkalinity is approximately 1.7 times higher than burial as a long-term carbon sink in a subtropical mangrove system. Fluxes of methane offset burial by approximately 6%, while the nitrous oxide sink was approximately 0.5% of burial. Export of dissolved organic carbon and particulate organic carbon to the coastal zone is also significant and combined may account for an atmospheric carbon sink similar to burial. Our results indicate that the export of DIC and alkalinity results in a long-term atmospheric carbon sink and should be incorporated into the blue carbon paradigm when assessing the role of these habitats in sequestering carbon and mitigating climate change.